2021
DOI: 10.1590/s0004-2803.202100000-34
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Functional Disorders in the Pre-Operatory Evaluation of Bariatric Surgery

Abstract: BACKGROUND: Obesity is an independent risk factor for esophageal symptoms, gastroesophageal reflux disease (GERD), and motor abnormalities. When contemplating bariatric surgery, patients with obesity type III undergo esophagogastroduodenoscopy (EGD) and also esophageal manometry (EMN), and prolonged pHmetry (PHM) as part of their pre-operative evaluation. OBJECTIVE: Description of endoscopy, manometry and pHmetry findings in patients with obesity type III preparing for bariatric surgery, and correlation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
1
1
1
Order By: Relevance
“…10,11 GERD symptoms were present in less than half (43.3%) of patients undergoing bariatric surgery. This percentage is similar to the one found by Lemme et al 12 (38%). but other studies report percentages as high as 62.5%.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…10,11 GERD symptoms were present in less than half (43.3%) of patients undergoing bariatric surgery. This percentage is similar to the one found by Lemme et al 12 (38%). but other studies report percentages as high as 62.5%.…”
Section: Discussionsupporting
confidence: 92%
“…Few studies assess manometric changes in patients subjected to bariatric surgery. The average LES pressure registered by Mora et al 12 in a 224 patients population (Table 4) with a mean BMI of 50.2 was higher (16 mmHg) than the mean encountered in the present study (9.79 ± 0.33 mmHg). Although esophageal dysmotility was found in 22.7% of our population (Table 5), other studies have reported a prevalence ranging between 33.4% and 66.1%.…”
Section: Discussioncontrasting
confidence: 69%
“…Our results confirm an important GERD prevalence of 21.6% among people with MO who are bariatric surgery candidates, a prevalence that can reach 29.4% if AET is taken into account together with the number of reflux episodes and MNBI. There are only a few prevalence studies based on pHmetric findings on patients with obesity, the most recent of which identify a GERD prevalence in MO around 35% taking into account the Lyon Consensus [30], or 52%-67% [31][32][33] with less strict AET cut-off points. However, there are no population studies on GERD prevalence based on pHmetric findings.…”
Section: Discussionmentioning
confidence: 99%